2019
DOI: 10.25105/ber.v18i2.5335
|View full text |Cite
|
Sign up to set email alerts
|

Compensation, Job Satisfaction and Employee Performance in Health Services

Abstract: <p><em>The objective </em><em>of this research is </em><em>to analyze the c</em><em>o</em><em>mpensation</em><em>,</em><em> job satisfaction and the </em><em>employees</em><em> performance of </em><em>Rumah Sakit Swasta in Jakarta</em><em>. Apart from that, the objective is also to an</em><em>alyse</em><em> the </em><em>effect of the c</em>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 9 publications
2
34
0
13
Order By: Relevance
“…Imbalan merupakan kompensasi dalam bentuk upah, insentif, dan reward yang diberikan kepada bidan setelah mereka memberikan kemampuan, keahlian serta usahanya kepada organisasi. Hasil riset Ramli (2018)…”
Section: Faktor Ekstrinsikunclassified
See 1 more Smart Citation
“…Imbalan merupakan kompensasi dalam bentuk upah, insentif, dan reward yang diberikan kepada bidan setelah mereka memberikan kemampuan, keahlian serta usahanya kepada organisasi. Hasil riset Ramli (2018)…”
Section: Faktor Ekstrinsikunclassified
“…Hasil empiris berikutnya menunjukkan tidak ada hubungan yang signifikan antara imbalan dengan kinerja. Hasil ini berlawanan dengan hasil riset Ramli (2018), Aspita & Sugiono (2018) serta Saban et al (2020). Gaji atau imbalan finansial yang diterima oleh seseorang bagi jasa-jasa yang diberikannya kepada organisasi dapat mengambil berbagai bentuk, jumlah imbalan finansial yang layak diterimanya berdasarkan jenjang pendidikan, pengetahuan, keterampilan, sifat pekerjaan, besarnya tanggung jawab dan wewenang (Robbins & Judge, 2013;Dessler, 2016).…”
Section: Pembahasanunclassified
“…Many studies have shown that employee satisfaction is a key element of performance [28,29]. Consequently, managers should devote part of their efforts to ensuring staff satisfaction.…”
Section: Area 5 Staff Satisfactionmentioning
confidence: 99%
“…Employee competency improvement can be made by conducting interrelated and continuous program management that focuses on improving the qualityof the program (Ramli and Maniagasi, 2018), especially those related to human resource development programs (Ramli, 2018b) Learning and Growth achievement of the HC program to achieve the stated business results of the company (Phillips, 2005;Ghazmahadi, Basri, Kusnadi and Ramli, 2020;Imran and Ramli, 2019).…”
Section: Employee Competencymentioning
confidence: 99%